Upaya Pencegahan Terhadap Tindak Pidana Kekerasan Seksual Pada Lingkungan Kampus - Megawati, Wenny; Faozi, Safik; Rochmani (Jurnal Ilmiah Penegakan Hukum, 2024)
This article aims to provide guidance for higher education institutions to formulate policies and take action to prevent and handle sexual violence related to the implementation of the Tridharma of Higher Education. The problem is focused on preventing criminal acts of sexual violence in the campus environment. Permendikbudristek Number 30 of 2021 has regulated protection in the form of prevention and how to handle it if sexual violence occurs in the campus environment. In order to approach this problem, theoretical references from Juridical Normativ are used. Data is collected through literature studies that are relevant to the latest material to be studied and analyzed qualitatively. This study concludes that universities are obliged to implement Permenristekdikti Number 30 of 2021 regarding sexual violence in the campus environment and in preventing criminal acts of sexual violence. Universities are obliged to make policies and implement them by creating a PPKS task force in order to create an independent campus, one of which is freedom from violence. sexual intercourse by prioritizing protection for the victim and not recurring.